A utilização de jogos matemáticos como recurso no ensino das quatro operações aritméticas. - GOMES, Kelliton da Silva (Universidade Federal do Tocantins, 2023)
The educational games are gaining ground in the classroom, in an attempt to seek playfulness into the schools. The game has a great utility when used well by teachers, it can be used to facilitate gaps in the process of learning mathematics, and has a great importance within the school environment helps to develop the ability of students to build their knowledge. Thus, the present study aims to investigate the possibilities of using games Shooting Game One and Mental Calculation, as a teaching resource in the teaching of the four Arithmetic operations. Regarding the methodological procedures it is an exploratory and descriptive field research, quantitative approach carried twenty-three students of the 6th year of elementary school at the State School Model. For data collection were applied two questionnaires containing five questions each and two games with a shot right and Mental Calculation. The results demonstrate that after application of games there has been progress in learning, especially in solving problems situations multiplication followed by addition and subtraction, and finally divide. To conclude, we can see that the math games are an important educational tool for teaching and learning, as they provide the student learning through playfulness.